Le jardinage urbain : le défi de la qualité des sols urbains pour les collectivités - Philippe Bodénan; Hugo Doux; Béatrice Béchet; Patrice Cannavo; Liliane Jean-Soro; Thierry Lebeau; Cécile Le Guern; Laure Vidal-Beaudet (Projets de Paysage)
Urban gardening is a booming trend. Local authorities are actively taking part in this movement in response to the demand of inhabitants but also because they see it as a way of addressing many of the challenges of the sustainable city. As a result, they are confronted with the issue of soil quality. Urban soils, as an environmental component, are rarely highlighted yet they are subjected to many constraints such as loss of agronomic potential or pollution. Based on experiments in Nantes, the article explores the process by which municipalities establish a diagnosis and intervene on soil quality, addressing the questions regarding the tools employed and the interactions with community gardeners. The approach adopted based on the landscape makes it possible to simultaneously address and, if necessary, establish the interrelations between the many challenges faced by communities in understanding urban soils, the skills required, and the difficulties in addressing the technical and political dimensions.